Mycotoxins in Plants and Plant Products Cocoa, Coffee, Fruits and Fruit Products, Medicinal Plants, Nuts, Spices, Wine - Weidenbörner, Martin (Springer International Publishing, 2018)
This book is one of three volumes that are an expansion of Mycotoxins in Foodstuffs, Second Edition, and it focuses on cocoa, coffee, fruits and fruit products, medicinal plants, nuts, spices, and wine. In addition all foodstuffs of plant origin except cereals and cereal products are covered. Mycotoxins in Plants and Plant Products - Cocoa, Coffee, Fruits and Fruit Products, Medicinal Plants, Nuts, Spices, Wine comprises: More than 280 new publications and 900 publications in all Each item includes "Co-contamination", showing the co-occurrence of mycotoxins in a foodstuff, where possible Each item includes "Further contamination", describing the same or further foodstuff/s with its/their mycotoxins documented, where possible Single chapter overview with all mycotoxins and their foodstuff-spectrum Single chapter overview with each single foodstuff and its mycotoxin-spectrum Separate list of the articles dealing with conventionally and organically produced foodstuffs and their mycotoxin contamination Numerical and Alphabetical Bibliography .